Feasibility and Accuracy of a Wearable Biosensor Device for Vital Sign Monitoring in Septic Emergency Department Patients in Rwanda. Issue Volume 34:Issue s1(2019) (May 2019) - Garbern, Stephanie; Mbanjumucyo, Gabin; Umuhoza, Christian; Sharma, Vinay; Mackey, James; Martin, Kyle; Twagirumukiza, Francois; Rosman, Samantha; McCall, Natalie; Wegerich, Stephan; Levine, Adam
Abstract : Introduction: Low and middle-income countries (LMICs) bear a disproportionately high burden of sepsis, contributing to an estimated 90% of global sepsis-related deaths. Critical care capabilities needed for septic patients, such as continuous vital sign monitoring, are often unavailable in LMICs. Aim: This study aimed to assess the feasibility and accuracy of using a small wireless, wearable biosensor device linked to a smartphone, and a cloud analytics platform for continuous vital sign monitoring in emergency department (ED) patients with suspected sepsis in Rwanda. Methods: This was a prospective observational study of adult and pediatric patients (≥ 2 months) with suspected sepsis presenting to Kigali University Teaching Hospital ED. Biosensor devices were applied to patients' chest walls and continuously recorded vital signs (including heart rate and respiratory rate) for the duration of their ED course. These vital signs were compared to intermittent, manually-collected vital signs performed by a research nurse every 6-8 hours. Pearson's correlation coefficients were calculated over the study population to determine the correlation between the vital signs obtained from the biosensor device and those collected manually. Results: 42 patients (20 adults, 22 children) were enrolled. Mean duration of monitoring with the biosensor device was 34.4 hours. Biosensor and manual vital signs were strongly correlated for heart rate (r=0.87, p<0.001) and respiratory rate (r=0.74 p<0.001). Feasibility issues occurred in 9/42 (21%) patients, although were minor and included biosensor falling off (4.8%), technical/connectivity problems (7.1%), removal by a physician (2.4%), removal for a procedure (2.4%), and patient/parent desire to remove the device (4.8%). Discussion: Wearable biosensor devices can be feasibly implemented and provide accurate continuous vital sign measurements in critically ill pediatric and adult patients with suspected sepsis in a resource-limited setting. Further prospective studies evaluating the impact of biosensor devices on improving clinical outcomes for septic patients are needed.